Sistem InFormasi Geografis Donor Darah (SIGDORAH) Menggunakan Pendekatan Togaf ADM - Purnamasari, P; Muslih, Muhamad; Sembiring, Falentino (STIKOM Tunas Bangsa Pematangsiantar, 2021)
The Blood donation is an activity of taking blood from someone voluntarily to be kept as stock or given to patients in need. Blood donation activities are channeled through the Blood Transfusion Unit (UTD) of the Indonesian Red Cross (PMI) which is engaged in blood donation services for the community in their respective regions. Lack of public awareness of blood donation and ineffective blood donation activities during the pandemic caused the blood stock supply at PMI Sukabumi Regency to be running low and even empty. The purpose of this research is to create a blood donor inFormation system that is equipped with a website-based Geographic InFormation System. GIS is used to store and display inFormation on potential donors in a digital map. This study uses the Togaf Architecture Development Method approach which was developed using the PHP Version 7 programming language, MySQL 3.2.2 database and open source Leafletjs. The result of this research is a website-based geographic inFormation system for blood donors (SIGDORAH).